Fe3O4 nanoplates/carbon network synthesized by in situ pyrolysis of an organic–inorganic layered hybrid as a high-performance lithium-ion battery anode. Issue 27 (15th June 2015) - Long, Zhao; Wei, Liu; Shuang, Liu; Jifei, Wang; Huanlei, Wang; Jiaxin, Chen
Abstract : Novel porous Fe3 O4 nanoplate@carbon composites have been fabricated by in situ pyrolysis of organic–inorganic layered hybrids. Abstract : Metal organic framework (MOF) pyrolysis is believed to be an excellent method to prepare porous metal oxide anode materials for lithium-ion batteries. However, some disadvantages such as expensive MOFs and the uncontrollable shape of metal oxides limit its further development. In this work, we reported a facile approach to prepare a porous Fe3 O4 /carbon composite material via in situ pyrolysis of cheap organic–inorganic layered precursors. Similar to those prepared by MOF pyrolysis, the as-obtained Fe3 O4 /C composite material has a highly porous carbon network, but contains novel Fe3 O4 nanoplates with polygonal shape embedded homogeneously within the carbon. The composite electrode exhibited a high reversible capacity of 1180 mA h g −1 at a current density of 100 mA g −1 . Moreover, it showed excellent cycling performance and high rate capability, which is supposed to benefit from the high electric conductivity, the buffering effect for the volume changes of porous carbon matrix and the short diffusion path of the Fe3 O4 nanoplates for rapid Li + ion supply.